Qualitative Performance Monitoring In Artistic Team Pencak Silat Category - Rahayuni Rahayuni; Putri Dwi Oktavianingrum; Imam Hariadi; Muhammad Atiq Noviudin Pritama (Indonesian Journal of Kinanthropology (IJOK), 2025)
Background: Pencak silat has been admitted as a branch of sport and projected to be officially competed in multievent sport games, hence the call integrating sport science in pencak silat has been conducted by pencak silat scholars and practitioners.  This research bracgrounded from the lack of reference for analyzing the performance of pencak  silat athletes in the artistic category, include team category. This study aims to develop a form to monitor the performance mastery  and development of synchronised movements in pencak silat athletes in the artistic team category. By using the forms, coaches can monitor movement errors in athletes, evaluate  them, and make improvements so that athletes can make progress in each training session to  achieve top performance. Methods: This study employs a descriptive  qualitative research method, analyzing the data of 3 (three) pencak silat team category who have participated in three championships from July to December 2024, resulting in nine documentation sets. The documentation then used as a starting point to develop[ a permormance monitoring tables contained 12 points in team category movements. Results: the results of this  study is a form to assess the progress of synchronicity and accuracy of time, rhythm, and refinement of movements in the team category. upon careful development, the forms could be used as a tools helping the coaches in monitoring progression in pencak silat team category.  Conclusions: , the forms could be used as a tools helping the coaches in monitoring progression in pencak silat team category.